Flow regimes and pressure drop of a composite tridimensional rotational flow sieve tray under concurrent gas‐liquid flow. Issue 10 (10th June 2022) - Zhang, Shaofeng; Liu, Bingfang; Wang, Hongkai; Liu, Yan; Wang, Dewu; Tang, Meng; Dai, Shijie
Abstract: A composite tridimensional rotational flow sieve tray (CTRST) is proposed. The flow patterns of CTRST were visually categorized, combined with the standard deviation of the pressure difference. In the TRST area of the internal packing‐type tray, the membrane‐drip column and foam‐embolic flow is present, while bubbly and milk froth‐ribbon flow is present in the packing area of the external packing‐type tray. The effect of the tray structure parameters on the pressure drop under co‐current flow was investigated. The dry and wet pressure drop is within 160 and 900 Pa, respectively. Under the same structural parameters, the pressure drop of the internal packing‐type tray was higher than that of the external packing‐type tray. The flow characteristics of the standard tray under the countercurrent flow were compared. The CTRST was found to be more suitable for co‐current flow. A prediction model pressure drop under co‐current was established with an error of 15.5%.